Milk Production, Quality Parameters, and Bacterial Colony Counts of Raw Milk from Murrah Buffaloes Reared in Mixed Crop-Livestock Systems - Ratni, Eli; Roza, Elly; Arief (Journal of Buffalo Science, 2024)
This research aimed to assess the quantity and quality of raw Murrah buffalo milk in a mixed crop-livestock farming system in North Sumatra, Indonesia. The study was conducted at the Sumber Ternak Abadi livestock farm in Pagar Merbau District, North Sumatra, Indonesia, established in 2012 within an oil palm plantation. The study observed 40 lactating Murrah buffaloes. Variables included milk production and quality metrics such as total plate count in colony-forming units per ml, water content percentage, total solids, fat content, and pH. Results demonstrated a milk yield standardized to 305 days ranging from 1,200.78±490.25 to 1,505.71±589.73 kg/head/lactation. The total plate count was 2.1 x 105 ± 0.32 CFU/ml, total solids were 16.87% (w/w), fat was 5.7% (v/v), and pH was 6.73. The results confirmed that the raw Murrah buffalo milk from the observed farm meets the Indonesian National Standard for milk quality. A significant positive correlation was found between water content and total bacterial colony count (r = 0.82, p < 0.01), suggesting that higher water content in milk correlates with increased bacterial colonies.